Extramedullary Hematopoiesis: An Unusual Finding in Subdural Hematomas - Rong Li; Vishnu V. B. Reddy; Cheryl Ann Palmer (Case Reports in Pathology)
We present a case of a 59-year-old man who was found to have clusters of hyperchromatic, small, round nucleated cells within a subdural hematoma removed after a skull fracture. Immunohistochemistry study confirmed that the cells were hematopoietic components predominantly composed of normoblasts. In this paper, we describe the clinical and pathological findings. A brief review of published information on extramedullary hematopoiesis in subdural hematoma and the mechanisms of pathogenesis are also discussed. While extramedullary hematopoiesis is seen anecdotally by neuropathologists in chronic subdural hematomas, only a few cases are documented in the literature. Furthermore, extramedullary hematopoiesis in subdural hematoma can pose a diagnostic challenge for general pathologists who encounter subdural hematoma evacuations seldom in their surgical pathology practices.